2018
DOI: 10.1016/j.ejor.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity tail risk and credit default swap spreads

Abstract: This is a repository copy of Liquidity tail risk and credit default swap spreads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The utilization of six time-varying copula models allows us to compare dynamic dependence patterns between sample countries. Recent papers in quantitative and mathematical finance have shown that copula models are flexible enough for modeling nonlinear dependence and tail risk (e.g., Grundke and Polle, 2012;Al Janabi et al, 2017;Irresberger et al, 2018). When fitting copula functions, we particularly suggest a new forcing variable to better model the dependence parameter of the 90-degree rotated Clayton and 270-degree rotated Clayton copulas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of six time-varying copula models allows us to compare dynamic dependence patterns between sample countries. Recent papers in quantitative and mathematical finance have shown that copula models are flexible enough for modeling nonlinear dependence and tail risk (e.g., Grundke and Polle, 2012;Al Janabi et al, 2017;Irresberger et al, 2018). When fitting copula functions, we particularly suggest a new forcing variable to better model the dependence parameter of the 90-degree rotated Clayton and 270-degree rotated Clayton copulas.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers in quantitative and mathematical finance have shown that copula models are flexible enough for modelling nonlinear dependence and tail risk (e.g. Al Janabi, Arreola Hernandez, Berger, & Nguyen, 2017; Grundke & Polle, 2012; Irresberger, Wei, & Gabrysch, 2018). When fitting copula functions, we particularly suggest a special forcing variable to better model the dependence parameter of the 90° rotated Clayton and 270° rotated Clayton copulas.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Escobar et al (2012) have offered a multivariate extension of the CreditGrades model under the assumption of stochastic variance and correlation among the companies' assets. Credit Default Swap is a topic of interest in much recent operational research literature (Guarin et al, 2011;Tomohiro, 2014;Cont and Minca, 2016;Chalamandaris and Vlachogiannakis, 2018;Koutmos, 2018;Irresberger et al, 2018), but in practice, models for traded CDS spreads tend not to be popular among portfolio managers. Although the aforementioned models provide very close approximations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In actuarial science, for example, Eckert and Gatzert (2018) model extreme losses using copulas to account for tail dependence ("ruin probability"). Coefficients of (usually lower) tail dependence have also been used in asset pricing by Rodriguez (2007); Okimoto (2008); Garcia and Tsafack (2011); Meine et al (2016); Chabi-Yo et al (2018); Irresberger et al (2018) to study the risk premia for crash events. Finally, at the macro level, De Jonghe (2010) and Patton (2017, 2018) employ measures of tail dependence to estimate the probability of a crash in the financial system.…”
Section: Introduction and Resultsmentioning
confidence: 99%